Hybrid Nanomaterials of Magnetic Iron Nanoparticles and Graphene Oxide as Matrices for the Immobilization of β-Glucosidase: Synthesis, Characterization, and Biocatalytic Properties - Orfanakis, Georgios; Patila, Michaela; Catzikonstantinou, Alexandra V.; Lyra, Kyriaki-Marina; Kouloumpis, Antonios; Spyrou, Konstantinos; Katapodis, Petros; Paipetis, Alkiviadis; Rudolf, Petra; Gournis, Dimitrios; Stamatis, Haralambos (Frontiers in Materials, 2018)
Hybrid nanostructures of magnetic iron nanoparticles and graphene oxide were synthesized and used as nanosupports for the covalent immobilization of β-glucosidase. This study revealed that the immobilization efficiency depends on the structure and the surface chemistry of nanostructures employed. The hybrid nanostructure-based biocatalysts formed exhibited a two to four-fold higher thermostability as compared to the free enzyme, as well as an enhanced performance at higher temperatures (up to 70°C) and in a wider pH range. Moreover, these biocatalysts retained a significant part of their bioactivity (up to 40%) after 12 repeated reaction cycles.